Animal Name Recognition Through Cooperative Learning for Elementary School Students - Siti Afidah (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2021)
The general research objective in this study is to investigate the learning of animal name recognition through cooperative learning in elementary school students. Initially, students were not familiar with various strategies and approaches, so that each student was able to repeat and understand the names - animal names easily. The research method used was classroom action research (CAR). The participants in this study were fifth-grade students, totalling 15 students. At the time the learning was carried out, the students still lacked understanding. When the pre-cycle of only five students from 15 students had passed with a percentage of 33%, the increase in knowledge continued to cycle 1, and ten students passed with a percentage of 66%. They continued Cycle II with improved planning, and accurate implementation had passed 15 students with a 100% percentage. With the Cooperative Learning model, the learning was easier to accept because there were smaller and more effective groups if the students had difficulties in learning.